Pembagian Warisan pada Masyarakat Adat Melayu Bunut dan Kedudukannya dalam Kompilasi Hukum Islam - Muslim Muslim (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
The law of inheritance is very closely related to the scope of human life because every human being has two conditions that are life and death. Most of the existing laws in the science of inheritance or Faraidh are related to death, so Faraidh can be said to be half of the existing knowledge, all people would need it, including the indigenous people of Malay Bunut. The tradition in the Malay Bunut community is a combination of the matrilineal Minangkabau system and the patriarchal Malay system. The majority of Bunut people claim to be from the Malay Peninsula, while some of them claim to be from Minangkabau. But in the kinship system, the Malay traditional community of Bunut is more inclined towards the matrilineal system and divided into several tribes. In the inheritance system, the daughter tends to get more from their parents. Nevertheless, boys control traditional practice. There are even cases of inheritance, where boys take all the inheritance from their parents without sharing it with their sisters. The article is intended to find out how the actual distribution of inheritance according to the Malay Bunut tradition is and the extent of the role of traditional leaders in the distribution of inheritance, as well as their position in the Compilation of Islamic Law.